PRIMARY MANAGEMENT OF BURNING MOUTH SYNDROME FOR GENERAL DENTIST (Review article) - Rinda Prawidiastuti; Nur Ismah Gitasari; Yunita Fatmala; Wahyu Hidayat; Indah Suasani Wahyuni (Dentino : Jurnal Kedokteran Gigi, 2019)
Background :Burning Mouth Syndrome (BMS) or also called Burning Tongue Syndrome is a chronic idiopathic condition, where the patient complains of pain and burning on the tongue or other oral mucosa. Purpose:The purpose of this paper is to determine the primary management that general dentists can do for patient with burning mouth syndrome in the form of a systematic literature review. Method: All of the articles reviewed were obtained from PubMed, Google Scholar and Science Direct search engines which were selected for publication in the past 10 years. Results: From a total of 30 articles obtained, 23 articles were found to be in accordance with the inclusion criterias, such as written in English, in the form of a Full Paper and only discussed BMS without systemic disease. Discussion: The primary management of patients with burning mouth syndrome that can be done by a general dentist is to determine the type of BMS so that a more specific treatment plan can be obtained. General dentists can provide communication, information and education (IEC) regarding BMS, and if necessary, analgesics in the form of topical lidocaine or benzydamine hydrochloride mouth rinse 0.15% can be given to reduce symptoms but only temporary, so that they need referrals to other competent experts. Conclusion: General dentists need to know and learn about various primary managements of Burning Mouth Syndrome cases, so that they can carry out treatment according to their competence.